2012
DOI: 10.3389/fnhum.2012.00319
|View full text |Cite
|
Sign up to set email alerts
|

More creative through positive mood? Not everyone!

Abstract: It is commonly assumed that positive mood improves human creativity and that the neurotransmitter dopamine might mediate this association. However, given the non-linear relation between dopamine and flexibility in divergent thinking (Akbari Chermahini and Hommel, 2010), the impact of mood on divergent kinds of creativity might depend on a given individual's tonic dopamine level. We tested this possibility in adults by assessing mood, performance in a divergent thinking task [the Alternate Uses Task (AUT)], and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 27 publications
8
72
1
Order By: Relevance
“…From a theoretical perspective, our experimental findings corroborate existing findings on the link between positive emotion and creative ideation [1,2,3], and extend these findings by showing a direct causal link between positive emotion and creative ideation, within subjects. Moreover, our research provides, for the first time, concrete evidence for a link between cognitive appraisal processes, positive emotion, and originality within the context under investigation.…”
Section: Discussion and Future Worksupporting
confidence: 89%
See 2 more Smart Citations
“…From a theoretical perspective, our experimental findings corroborate existing findings on the link between positive emotion and creative ideation [1,2,3], and extend these findings by showing a direct causal link between positive emotion and creative ideation, within subjects. Moreover, our research provides, for the first time, concrete evidence for a link between cognitive appraisal processes, positive emotion, and originality within the context under investigation.…”
Section: Discussion and Future Worksupporting
confidence: 89%
“…Focusing on temporal ways of assessing emotion [e.g. 22] could help explain how the rate of appraisals over time might be used to guide the intensity of an emotion, which could be effective since intensity in particular might hold the key to further augmenting task performance [1].…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…joy or pride) is generated by the subjective evaluation that an event is conducive to the goals of an individual [26]. This stimulates dopamine release in the mesocortical and mesolimbic areas of the brain, which is associated with an increase in the flexibility with which information is relayed to other brain areas [1]. The resulting increase in flexibility makes it easier to 1) generate many and diverse ideas, a marker for creativity during the idea generation step in the creative process, and 2) gain creative insights as measured by insight problem solving tasks [2] (Figure 1).…”
Section: Emotion and Creativitymentioning
confidence: 99%
“…Moreover, many neurological studies have shown that education or training can improve both convergent and divergent thinking, whereas problem-solving can be tackled by manipulation without requiring education or training (Deininger et al, 2012): see Fink et al (2010Fink et al ( , 2012, Jung et al (2010a), Heidarie et al (2011), Kröger et al (2013), Luo et al (2013), Wei et al (2014) on divergent thinking, and see Spencer et al (2013) and Ukkola-Vuoti et al (2013) on convergent thinking. Note that sleep (Ritter et al, 2012) and mood (Akbari Chermahini & Hommel, 2012) have been shown to affect creativity. In this paper, I will not account for these factors.…”
Section: Introductionmentioning
confidence: 99%